Effects of Light Sources and Intensity on Broilers Grown to Heavy Weights: Hematophysiological and Biochemical Assessment - Olanrewaju , Hammed A.; Collier, Stephanie D.; Purswell, Joseph L.; Branton, Scott L. (International Journal of Poultry Science, 2016)
Background: Most governments around the world including the USA have passed measures to phase out incandescent light bulbs in favor of more energy-efficient lighting alternatives. Research is limited on blood physiological variables of broilers grown to heavy weights (>3 kg) under these new light sources to ensure health and welfare of broilers. Objective: We investigated the effects of light sources and intensity on blood physiological and biochemical variables of broilers grown to heavy weights. Methodology: In each of 4 trials having 2 replicates per trial, 960 1 day old ross×ross 708 chicks were randomly distributed into 16 rooms (30 male and 30 female per room). A 4×2 factorial treatment structure evaluated 4 light sources [incandescent (ICD, standard), compact fluorescent (CFL), Light Emitting Diode (LED) and poultry specific filtered LED (PSF-LED)] from day 1-56 and 2 levels of light intensities (5 and 20 lx) from day 22-56 of age at 50% RH. Feed and water were provided ad libitum. Blood samples were collected from wing brachial vein on day 14, 21, 28, 42 and day 56 of age and analyzed immediately. Results: Light sources had effect (p